First record of Lophodinium polylophum (Daday) Lemmermann 1910 (Dinophyceae: Lophodiniaceae) in Peru - Samanez, Iris (2015)
Herein, the first record of Lophodinium polylophum from Peru is presented. This fresh water dinoflagellate was identified in plankton samples from the lagoon Picoplancha of Santuario Nacional Pampas del Heath (Madre de Dios) and from a stream in the Puinahua River basin in Loreto.